Characterization of the Polysaccharide from Adhesive Discs of Parthenocissus tricuspidata - Zhang, L.; Deng, W.L. (Asian Journal of Chemistry, 2012)
A water-soluble polysaccharide (PT2) was isolated from adhesive discs of Parthenocissus tricuspidata and its structure was determined by monosaccharide analysis, methylation, periodate oxidation, Smith degradation and IR spectrum. Some advanced structure of PT2, such as honeycomb structure and individual polysaccharide, were observed by atomic force microscopy (AFM). We also evaluate the adhesive property of PT2 and the results suggested that it was a potential bio-adhesive with the highest adhesion force value of 295.8 nN.